Gender and politics. Review of theoretical and empirical debates in Santa Fe and Entre Ríos (2000-2022) (Papeles, 2023)
Over the last decades, the link between gender and politics has been studied in depth from different perspectives and through international, national, and subnational research. This paper aims to systematize the main contributions from gender and political studies, focusing on trends in the provinces of Santa Fe and Entre Ríos. To provide a fair outline of the literature production about Gender and Politics, different sources were reviewed including, for instance, final degree projects and theses written for Bachelor's degrees in Political Science, PhD theses, books or chapters of books, work papers from research groups and papers presented at political science-related conferences. In conclusion, it should be noted that gender and politics analysis developed in Santa Fe and Entre Ríos is relatively new and it has emerged in the last five years. Even though the access to information is severely limited, there are great possibilities for the development of comparative studies between these provinces.
Keywords: Gender; Politics; subnational studies; Santa Fe; Entre Ríos